2009
DOI: 10.1152/ajprenal.90217.2008
|View full text |Cite
|
Sign up to set email alerts
|

Direct action of aldosterone on bicarbonate reabsorption in in vivo cortical proximal tubule

Abstract: The direct action of aldosterone (10(-12) M) on net bicarbonate reabsorption (J(HCO(3)(-))) was evaluated by stationary microperfusion of an in vivo middle proximal tubule (S2) of rat kidney, using H ion-sensitive microelectrodes. Aldosterone in luminally perfused tubules caused a significant increase in J(HCO(3)(-)) from a mean control value of 2.84 +/- 0.08 [49/19 (n degrees of measurements/n degrees of tubules)] to 4.20 +/- 0.15 nmol.cm(-2).s(-1) (58/10). Aldosterone perfused into peritubular capillaries al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…The proximal tubule is responsible for the reabsorption of 80% of the filtered bicarbonate, a process that depends on the secretion of H ϩ ions by two major mechanisms: the Na ϩ /H ϩ exchanger and H ϩ -ATPase (4,35,39). Recently, studies from our laboratory demonstrated genomic and nongenomic effects of aldosterone on the Na ϩ /H ϩ exchanger in in vivo S2 (25) and in isolated S3 (19) segments of proximal tubule. However, the action of this hormone on H ϩ -ATPase in the proximal tubule is not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The proximal tubule is responsible for the reabsorption of 80% of the filtered bicarbonate, a process that depends on the secretion of H ϩ ions by two major mechanisms: the Na ϩ /H ϩ exchanger and H ϩ -ATPase (4,35,39). Recently, studies from our laboratory demonstrated genomic and nongenomic effects of aldosterone on the Na ϩ /H ϩ exchanger in in vivo S2 (25) and in isolated S3 (19) segments of proximal tubule. However, the action of this hormone on H ϩ -ATPase in the proximal tubule is not known.…”
mentioning
confidence: 99%
“…However, the receptor involved in the rapid responses to aldosterone is unknown and has been the theme of discussions (13); recently, data from our laboratory suggest that the glucocorticoid receptor (GR) can participate in nongenomic effects of aldosterone on the proximal tubule (19,25). A role for aldosterone in regulating calcium homeostasis is uncertain, but a rise in intracellular Ca 2ϩ concentration ([Ca 2ϩ ] i ) is a component of several effects of aldosterone, as a second messenger on the hormonal nongenomic effects and as a prerequisite for the genomic action (3,13,19,25,29,36,38).…”
mentioning
confidence: 99%
“…Apical Na + channel activity is the limiting step in the transport process, and it is likely that ALDO ultimately acts to increase the open time of existing ion channels and/ or increase the total number of such channels [225]. However, other protein targets have also been identified, including i) a luminal NHE3 exchanger in the colon [226,227] and the proximal tubule [228] and a basolateral NHE1 in the proximal tubule [229,230], ii) an Na + /K + -ATPase in human kidney proximal tubule (HKC11) cells [231], iii) a luminal thiazide-sensitive Na + /Cl − cotransporter in the distal renal tubule that appears to mediate Na+ reabsorption in response to volume depletion [232], and iv) a renal proximal H + -ATPase [233].…”
Section: Classic Genomic Actions Of Aldomentioning
confidence: 99%
“…The physiological and clinical relevance supporting these rapid effects remains unclear, but their existence has been described in various target organs and cells, including amphibian skin and urinary bladders [258,259], vascular smooth muscle cells and endothelial cells [260], skeletal muscle cells [261], human mononuclear leukocytes [262], cardiac myocytes [263], skin fibroblasts from MR-knockout mice [256], colonic epithelial cells [264] and isolated colonic crypts [265]. Several sites in the kidney, particularly cultured kidney cells, have been shown to be sensitive to non-genomic ALDO action [266], including principal cells that were freshly isolated from rabbits [267], the human distal colon [268], in vivo renal proximal tubules (S2 segment) [228], isolated renal proximal tubules (S3 segment) [229,233], medullary thick ascending limbs [269] and renal collecting duct cells [270]. Its non-genomic actions include effects on signal transduction pathways and ion transporters, such as the epithelial Na + channel [267], the Na + /H + exchanger [228,229,271,272] and the vacuolar H + -ATPase [230,233,258,259,273].…”
Section: Non-genomic Actions Of Aldomentioning
confidence: 99%
See 1 more Smart Citation